2011
DOI: 10.1007/s10943-011-9563-8
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity for Promotion of Behaviors Likely to Reduce New HIV Infections in Uganda: A Study Among Muslim Youth in Wakiso District

Abstract: The study was done to determine the association between religiosity and behaviors likely to reduce new HIV infections among 1,224 Muslim youth. Respondents with Sujda, the hyperpigmented spot on the forehead due to prostration during prayers, were more likely to abstain from sex, be faithful in marriage, and avoid alcohol and narcotics. Males wearing a Muslim cap were more likely to abstain from sex and avoid alcohol and narcotics. Females wearing the long dress (Hijab) were also more likely to avoid alcohol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…There is another possibility that more frequent religious practices leaves less time for alcohol consumption. Results in the study are similar to the findings by Kagimu et al (2011) in which he found that Muslim youths who attended religious services were less likely to consume alcohol compared with those who did not participate (Kagimu et al, 2011). In a related sero-behavioral-religiosity survey in Uganda, it was found that Muslims were less likely to drink alcoholic beverages when compared with Christians and those who prayed or attended religious services were less likely to drink alcohol when compared with those who did not (Kagimu et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…There is another possibility that more frequent religious practices leaves less time for alcohol consumption. Results in the study are similar to the findings by Kagimu et al (2011) in which he found that Muslim youths who attended religious services were less likely to consume alcohol compared with those who did not participate (Kagimu et al, 2011). In a related sero-behavioral-religiosity survey in Uganda, it was found that Muslims were less likely to drink alcoholic beverages when compared with Christians and those who prayed or attended religious services were less likely to drink alcohol when compared with those who did not (Kagimu et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Eight studies examined condom use in association with service attendance [49][50][51][52][53][54][55][56]. Five of those eight studies (62%) documented a positive/protective association and were statistically significant [49,51,52,54,56]. The most frequent mechanism reported among studies that documented a protective association was beliefs and values related to sex or sexuality and social influence.…”
Section: Expanded Details From Statistical Analysismentioning
confidence: 99%
“…Influence of religion on behavior. Eleven studies examined condom use in association with the influence of religion on behavior [42,49,50,[54][55][56][60][61][62][63][64]. These studies were mostly mixed methods (n = 7).…”
Section: Plos Onementioning
confidence: 99%
“…Such religiosity has been reported in previous studies to facilitate HIV preventive behaviors in the general population and good treatment outcomes among PLWH. [30][31][32][33] In the context of HIV care in Tanzania currently, individual religiosity issues are not often looked at. This could easily be addressed during individual counseling sessions to increase its potential benefits to PLWH.…”
Section: Discussionmentioning
confidence: 99%